Asuhan Kebidanan Continuity of Care (CoC) dengan Bendungan ASI pada Ny. L.M. - Carvalho, Filomena de; Sofiyanti, Ida (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2024)
The Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are crucial indicators in developing country's health status, especially in developing countries like timorense. Despite a decrease, MMR and IMR in Timor Leste remain high, with the Sustainable Development Goals (SDGs) target of 70 per 100,000 live births for MMR and 12 per 1,000 live births for IMR. In Timorense , in 2015, there was an increase in MMR to 570 per 100,000 live births and IMR to 25 per 100,000 live births. The primary causes of MMR are pre-eclampsia/eclampsia and hemorrhage, while the main causes of IMR are low birth weight (LBW) and asphyxia. To address this issue, efforts are made to ensure that every mother and baby receives quality comprehensive midwifery care, including integrated antenatal care (ANC), delivery assistance by trained health personnel, postnatal care, and family planning services. Indonesia has implemented the Continuity of Care (CoC) program, which provides continuous care from pregnancy to family planning, proven effective in reducing mortality and morbidity rates. Based on this background, the author conducts a case study "Midwifery Care Through Continuity of Care for Mrs. L.M in RT 03Veira mar Village" to apply theoretical and practical knowledge, with the expectation of improving the quality of prospective health workers and the health of mothers and infants in Timorense.   Abstrak Angka Kematian Ibu (AKI) dan Angka Kematian Bayi (AKB) merupakan indikator penting dalam menilai derajat kesehatan di suatu negara berkembag, AKI dan AKB di Timor Leste masih tinggi. Pada tahun 2015, 215 per 100.000 dan AKB 25 per 100.000 dengan target Sustainable Development Goals (SDGs) yaitu AKI 70 per 100.000 kelahiran hidup dan AKB 12 terjadi peningkatan AKI menjadi 570 per 100.000 KH dan AKB menjadi 25 per 100.000 KH. Penyebab utama per 1.000 kelahiran hidup. Angka kematian ibu (AKI) dan AKB di Timor Leste masih tinggi, AKI 570 per 100.000 kelahiran hidup dan AKB 25 per 1.000 kelahiran hidup. Di Timor Leste, pada tahun 2015 AKI adalah pre-eklamsi/eklamsi dan perdarahan, sedangkan penyebab utama AKB adalah BBLR dan asfiksia. Timor Leste AKI dan AKB yaitu AKI 94 per 100.000 kelahiran hidup dan AKB 25 per 1.000 kelahiran hidup, pada tahun 2015 terjadi peningkatan AKI menjadi 215 per 100.000 KH dan AKI meningkat 570 per 100.000 dan AKB menjadi 25 per 100.000 KH. Penyebatama AKI adalah pre-eklamsi/eklamsi dan perdarahan,dan  penyebab utama AKB  adalah BBLR dan asfiksia.